2019
DOI: 10.1002/hlca.201900021
|View full text |Cite
|
Sign up to set email alerts
|

Configurational Lability of Imino‐Substituted Ethano Tröger Bases. Insight on the Racemization Mechanism

Abstract: Polycyclic indoline‐benzodiazepines are afforded in one step by the reaction of Tröger bases with N‐sulfonyl‐1,2,3‐triazoles under Rh(II) catalysis. After α‐imino carbene formation, the process involves a cascade of [1,2]‐Stevens rearrangement, Friedel‐Crafts, Grob fragmentation, and aminal formation reactions. It is highly diastereoselective (d.r. >49:1, four stereocenters incl. two bridgehead N‐atoms). However and in contrast with other reported carbene additions to these moieties, full racemization occurs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…All rights reserved. 22 Next to ring expansion reactions of N-heterocycles, this strategy can also be employed to the construction of new N-heterocycles as initially described by West (cf. Scheme 4).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…All rights reserved. 22 Next to ring expansion reactions of N-heterocycles, this strategy can also be employed to the construction of new N-heterocycles as initially described by West (cf. Scheme 4).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This observation indicates racemization not only in the initial ring-opening step, but also in the reversible aza-Mannich reaction (Scheme 8, c). 22 In addition to ring-expansion reactions of N-heterocycles, this strategy can also be employed for the construction of new N-heterocycles, as initially described by West (cf. Scheme 4).…”
Section: Short Review Synthesismentioning
confidence: 99%
“… 6 Of special interest to the current study, Tröger bases were shown to react and yield polycyclic indoline-benzodiazepines through a cascade of [1,2]-Stevens, Friedel–Crafts, Grob and aminal formation reactions ( Scheme 1 , top, a). 7 Also, 1,3,5-triazinanes form octahydro-1 H -purine derivatives via formal [6 + 3] cycloaddition, ring-closure and rearrangements ( Scheme 1 , top, b). 8 Herein, in a new development, the intermolecular reactivity of N -sulfonyl-1,2,3-triazoles 1 with imidazolidines 2 is reported ( Scheme 1 , bottom).…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition of diazo compounds in the presence of nitrogen Lewis bases is a recognized strategy to generate ammonium ylides efficiently. These intermediates react generally further following Stevens rearrangements to generate attractive nitrogen-containing scaffolds. Recently, it was shown that the addition of the α-imino diazo derivatives, generated from N -sulfonyl-1,2,3-triazoles precursors, to Tröger bases (TB) 1 leads to interesting polycyclic benzodiazepine-indoles 2 in a single step via a highly diastereoselective cascade of reactions (Scheme ). , …”
mentioning
confidence: 99%
“…Compounds 2 adopt a bowl-shaped geometry with the 5-, 6-, and 7-membered rings forming a rigid cup-like motif footed by the aromatic Ar substituent. Recently, studying benzodiazepinoindoles 2 further, these derivatives were found to be strongly chemically stable and resistant to both acid and oxidative conditions . In fact, hydrolysis of the aminal bridge of compounds 2 could not be realized using standard procedures.…”
mentioning
confidence: 99%